Perbandingan Pengupasan Material Overburden Berdasarkan Data Aktual, Data Ritase dan Data Survey pada Bukit Everest PT. ANTAM TBK. UBPN Sulawesi Tenggara - Qhori Dies Hardila; Ansosry Ansosry; Riko Maiyudi (Journals Mining Engineering : Bina Tambang, 2021)
Abstract One of the state-owned companies engaged in nickel mining is PT. ANTAM Tbk. UBPN SULTRA. The nickel mining area is located in Pomalaa District, Kolaka Regency, Southeast Sulawesi. The mining system applied to nickel mining is open pit mining with open pit and open cast methods. Differences in production results from the data recorded by the checker and the survey team. These differences lead to reconciliation where the calculation of annual reserves is not appropriate. The results of the cycle time calculation obtained a production result of 94.000,98 tons, the result of the calculation of the record (truck count) is the amount of transportation equipment ratio of 93.000,9 tons, and the volume of overburden from the survey measurement results on February 3 - March 18, 2020, which is 94735.65 tons. There is a difference in the volume of survey data and the ritase is greater than the survey and cycle time, from the difference in volume there is a smaller ritase volumeKeywords: Nickel, Cycle Time, Transport Equipment Ritase, Survey, and Overburden